1991
DOI: 10.1111/j.1528-1157.1991.tb05605.x
|View full text |Cite
|
Sign up to set email alerts
|

Kindling Susceptibility and Genetic Seizure Predisposition in Inbred Mice

Abstract: Olfactory bulb kindling rates were studied in two inbred strains of genetically seizure-prone mice (DBA/2 and El) and in three non-epileptic inbred strains [C57BL/6 (B6), ddY, and C3H/He (C3H)]. None of the DBA/2 mice had been stimulated to seizure before or during the kindling and all mice were studied at 4-6 weeks of age, before development of spontaneous or movement-induced seizure activity in the El strain. The audiogenically seizure-susceptible DBA/2 mice required the fewest number of stimulations to reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1

Year Published

1993
1993
2017
2017

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 28 publications
1
10
1
Order By: Relevance
“…We found that the mean litter size, 3.3±1.4, of Coil −/− mating pairs was significantly smaller than that of wild-type mating pairs, 6.9±2.2 (Figure 1A). Importantly, the average litter size of the wild-type C57BL6/J mating pairs was in good agreement with published data for C57BL6/J mice [36]. Thus, coilin knockout females have fewer pups per litter than do their wild-type counterparts.…”
Section: Resultssupporting
confidence: 88%
“…We found that the mean litter size, 3.3±1.4, of Coil −/− mating pairs was significantly smaller than that of wild-type mating pairs, 6.9±2.2 (Figure 1A). Importantly, the average litter size of the wild-type C57BL6/J mating pairs was in good agreement with published data for C57BL6/J mice [36]. Thus, coilin knockout females have fewer pups per litter than do their wild-type counterparts.…”
Section: Resultssupporting
confidence: 88%
“…By means of CCEP, we demonstrated a human cortico-cortical network connecting 1) anatomical homologous areas of the lateral and medial motor cortex along the rostro-caudal cognitive-motor gradient [3739] (e.g., supplementary motor area (SMA) to the caudal lateral premotor/primary motor (MI) area, pre-SMA to the rostral lateral premotor area), and 2) the somatotopically homologous regions in the lateral and medial motor cortices (e.g., the face SMA to the precentral hand face area) in a reciprocal manner [20]. Clinically, these circuits could account for the propagation of epileptic discharge from/into SMA [40] and the atypical motor responses infrequently seen in standard cortical stimulation: tonic and clonic responses in MI and SMA stimulation, respectively [41]. Functionally, it was not only the dorsal premotor area (mainly the caudal superior frontal gyrus and adjacent precentral gyrus) but also the ventral premotor area (mainly the caudal inferior frontal gyrus and adjacent precentral gyrus) that connected to the pre-SMA and SMA.…”
Section: Ccep Methodologymentioning
confidence: 99%
“…In a subsequent study [113], olfactory bulb kindling rates were studied in two inbred strains of genetically seizure-prone mice (DBA/2 and EL) and in three non-epileptic inbred strains (B6, ddY, and C3H/He). The seizure sensitive DBA/2 strain required the fewest number of stimulations to reach stage 5 seizures, whereas C3H/He mice required the most stimulations to reach stage 5 seizures.…”
Section: Interstrain Differences In the Expression Of Seizures Andmentioning
confidence: 99%